Application of a judgement method to regulatory impact assessments for sprinkler protection to English high‐rise residential buildings. (20th July 2020) - Arnott, Matthew; Hopkin, Danny; Spearpoint, Michael
Summary: When proposing a widespread investment in a safety measure, it is common for some form of regulatory impact assessment to be undertaken. In this study, the cost‐effectiveness of two proposals made by government bodies in England are investigated. The first is made by the London Assembly Planning Committee (LAPC) to retrofit London's existing high‐rise residential buildings (HRRBs) with sprinkler systems. Similarly, the Ministry of Housing, Communities and Local Government (MHCLG) has called for evidence to support reducing the trigger height for sprinkler provision in new HRRBs. The redundant concept of a value for a preventable fatality is addressed using the J ‐value methodology. The baseline results show a J ‐value above unity for both proposals, suggesting that they are potentially not cost‐effective. A sensitivity analysis highlights the embedded uncertainty and the implications for the J ‐value. For the MHCLG proposal, a large increase in annual fatalities for HRRBs would be required to support a reduction in trigger height for the inclusion of sprinklers. However, reasonable modification of some inputs results in a J ‐value below unity for the LAPC proposal, suggesting that this may be a cost‐effective safety investment. It may be argued that this proposal be implemented to err on the side of caution.